SEMA6B variants cause intellectual disability and alter dendritic spine density and axon guidance. Issue 19 (23rd May 2022) - Cordovado, Amélie; Schaettin, Martina; Jeanne, Médéric; Panasenkava, Veranika; Denommé-Pichon, Anne-Sophie; Keren, Boris; Mignot, Cyril; Doco-Fenzy, Martine; Rodan, Lance; Ramsey, Keri; Narayanan, Vinodh; Jones, Julie R; et al.
Abstract: Intellectual disability (ID) is a neurodevelopmental disorder frequently caused by monogenic defects. In this study, we collected 14 SEMA6B heterozygous variants in 16 unrelated patients referred for ID to different centers. Whereas, until now, SEMA6B variants have mainly been reported in patients with progressive myoclonic epilepsy, our study indicates that the clinical spectrum is wider and also includes non-syndromic ID without epilepsy or myoclonus. To assess the pathogenicity of these variants, selected mutated forms of Sema6b were overexpressed in Human Embryonic Kidney 293T (HEK293T) cells and in primary neuronal cultures. shRNAs targeting Sema6b were also used in neuronal cultures to measure the impact of the decreased Sema6b expression on morphogenesis and synaptogenesis. The overexpression of some variants leads to a subcellular mislocalization of SEMA6B protein in HEK293T cells and to a reduced spine density owing to loss of mature spines in neuronal cultures. Sema6b knockdown also impairs spine density and spine maturation. In addition, we conducted in vivo rescue experiments in chicken embryos with the selected mutated forms of Sema6b expressed in commissural neurons after knockdown of endogenous SEMA6B . We observed that expression of these variants in commissural neurons fails to rescue the normal axon pathway. In conclusion, identification of SEMA6B variants in patients presenting with an overlapping phenotype with ID and functional studies highlight the important role of SEMA6B in neuronal development, notably in spine formation and maturation and in axon guidance. This study adds SEMA6B to the list of ID-related genes. Graphical Abstract: